Bentuk Pengungkapan Citraan pada Aspek Kejiwaan dalam Sajak Penyair Jambi Dimas Arika Miharja - Sumiharti, Sumiharti; Amral, Sainil (Universitas Batanghari Jambi, 2023)
This research is included in the type of descriptive research with a content analysis approach to documents in the form of poetry literary works. The purpose of this study is to describe the type of image revealing psychological aspects contained in the poems of Jambi poet Dimas Arka Mihardja. The primary data in this study are words or sentences in the form of expressions contained in poems by Jambi poet Dimas Arka Mihardja which are related to the image of revealing psychological aspects. While the source of data in this study is Â the Anthology of Jambi Poetry Poems by Dimas Arka Mihardja. Research data were collected using documentation study techniques. The research data were analyzed using document analysis techniques that rely on rhyme discourse containing psychiatric aspects. From the results of the study, it was found that the poems of Jambi poet Dimas Arka Mihardja contained many forms of imaging revealing psychological aspects in the form of visual images, auditory images, olfactory images, taste images and motion images. Psychiatric aspects found include depression, obsession, irritation, fear, frustration, hope, attention, and anxiety.Â